PERENAPAN MODEL PEMBELAJARAN SOMANTIS AUDITORI VISUAL INTELEKTUAL (SAVI) UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V SDN CIPARAY - Mulyana, Rohmat; Pratama, Febri Fajar; Z, Rizki Hadiwijaya (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study was motivated by the low level of active student participation in the learning process. It is a Classroom Action Research (CAR) conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. Data collection techniques included observation, interviews, and documentation, while the data were analyzed using both quantitative and qualitative approaches. The purpose of this research was to improve students’ learning engagement through the implementation of the Somatic, Auditory, Visual, and Intellectual (SAVI) learning model in the Pancasila Education subject for fifth-grade students at SDN Ciparay. The findings indicate a significant increase in students’ active participation. In the pre-cycle condition, only 12 out of 28 students (42.86%) were categorized as active in the learning process. After the implementation of the SAVI model in the first cycle, student engagement increased to 67.86%, and in the second cycle, it further improved to 85.71%. The level of student engagement, which was initially dominated by the